Studi Tentang Pembinaan Akhlak Pada Peserta Didik Melalui Kegiatan Ekstrakulikuler Di SMA Taruna Tunas Bangsa Baturaja Ogan Komering Ulu Sumatera Selatan - Amri Ashadi; Abdul Roni; Supatmi; Suci Hartati (UNISAN JURNAL, 2022)
The Board of Trustees has not entirely formulated a development program to the extracurricular achievement indicators, the implementation of meetings that are less than optimal, have not yet established coordination between coaches regarding the extracurricular agenda. This study aims to uncover the processes of planning, implementing, evaluating, and the results of the moral development of students through extracurricular activities at SMA Taruna Tunas Bangsa Baturaja Ogan Komering Ulu Sumatera Selatan. The research method used is qualitat ive. Data collection techniques use structured interviews, participatory observation, and documentation studies. The results of the study show; first, planning is carried out at the general meeting at the beginning of the academic year covering the formulation of the activity agenda, competency in extracurricular achievements, budget; second, the implementation of fostering students in instilling the values of character akhlak karimah through motivation, giving examples/exemplary behavior and sharings among members; third, the overall evaluation will be held at the end of the semester deliberation meeting with the entire civitas academic. Assessment is carried out through daily behavior and reports from guardian parents; fourth, the results of coaching, namely: fair competition, maintaining the good name of the institution, being on time, obeying the guidance of Allah and the Prophets, high fighting spirit, never giving up, tolerance, careful, thorough, objective, discipline, responsibility, compassion, mutual assistance mutual cooperation, faithfulness, mutual respect, courtesy, honesty and fairness.